Effects of FTY720 and rapamycin on inflammation in taurocholate-induced acute pancreatitis in the rat - Müller, Christophe André; Belyaev, Orlin; Werner, Jens (Pancreas, 2012)
Objectives This study aimed at T-cell inhibition by immunosuppressants to reduce cell damage and improve the course of severe acute pancreatitis (SAP). Methods A taurocholate-induced SAP was used and 5 groups were compared: (1) rapamycin + FTY720, (2) rapamycin, (3) FTY720, (4) cortisol, and (5) control: sodium chloride. Drugs were applied intravenously at SAP induction; 6 hours later, rats were killed. Interleukin (IL)-1, IL-6, IL-10, tumor necrosis factor α, platelet-activating factor, amylase, and lipase were measured in serum and myeloperoxidase tissue activity in pancreas, kidney, lung, liver, and spleen. Edema, inflammation, and necrosis were histologically determined in pancreas. CD4/CD8 immunohistochemistry was performed. Results Inflammation was ameliorated in all 4 treated groups. Necrosis development was suppressed by FTY720, FTY720 + rapamycin, and cortisol. IL-6 and IL-10 were significantly lower in these groups. Amylase was higher in all treatment groups compared to the controls except for the cortisol group. Tumor necrosis factor α, lipase, and myeloperoxidase activity were not affected by therapy. CD4+/CD8+ cells were significantly less in FTY720-treated pancreata. Conclusion Rapamycin and FTY720 ameliorated the severity of SAP, which may be due to early suppression of helper T cells. FTY720 reduced the development of pancreatic necrosis. The combination of both immunosuppressants did not show advantage to treatment with FTY720 alone.